Curcumin Mediated Attenuation of Carbofuran Induced Oxidative Stress in Rat Brain - Jaiswal, Sunil Kumar; Sharma, Ashish; Gupta, Vivek Kumar; Singh, Rakesh Kumar; Sharma, Bechan (Biochemistry Research International, 2016)
The indiscriminate use of carbofuran to improve crop productivity causes adverse effects in nontargets including mammalian systems. The objective of this study was to evaluate carbofuran induced oxidative stress in rat brain stem and its attenuation by curcumin, a herbal product. Out of 6 groups of rats, 2 groups received two different doses of carbofuran, that is, 15 and 30% of LD50, respectively, for 30 days. Out of these, 2 groups receiving same doses of carbofuran were pretreated with curcumin (100 mg/kg body weight). The levels of antioxidants, TBARS, GSH, SOD, catalase, and GST were determined in rat brain stem. The 2 remaining groups served as placebo and curcumin treated, respectively. The data suggested that carbofuran at different doses caused significant alterations in the levels of TBARS and GSH in dose dependent manner. The TBARS and GSH contents were elevated. The activities of SOD, catalase, and GST were significantly inhibited at both doses of carbofuran. The ratio of P/A was also found to be sharply increased. The pretreatment of curcumin exhibited significant protection from carbofuran induced toxicity. The results suggested that carbofuran at sublethal doses was able to induce oxidative stress in rat brain which could be attenuated by curcumin.